Anxiety levels of patients undergoing coronary procedures in the catheterization laboratory. (1st February 2017) - Delewi, Ronak; Vlastra, Wieneke; Rohling, Wim J.; Wagenaar, Tineke C.; Zwemstra, Max; Meesterman, Martin G.; Vis, Marije M.; Wykrzykowska, Joanna J; Koch, Karel T.; de Winter, Robbert J.; Baan, Jan; Piek, Jan J.; et al.
Abstract: Background: High levels of anxiety are associated with worse outcomes in coronary artery disease patients. Little is known about anxiety levels in patients undergoing coronary procedures. Our objective is to examine the levels of anxiety in patients undergoing coronary angiography (CAG) or percutaneous coronary intervention (PCI) during the different phases of hospital stay and to evaluate which patient characteristics are associated with increased anxiety. Methods: Patients undergoing CAG or PCI between April 2009 and April 2010 were included in this prospective cohort study. Anxiety levels were measured using the self reported Visual Analogue Scale (VAS) of Anxiety, ranging from 0 to 100. VAS anxiety scores were obtained at hospital intake, pre- and post-procedure, and at hospital discharge. Multivariate linear regression analyses were performed to assess correlations between baseline characteristics and anxiety levels at the different time points. Results: In total 2604 patients were included, with 70.4% male participants with a mean age of 65 ± 12 years. VAS anxiety scores were highest pre-procedure (44.2 ± 27.0 mm). Female patients reported a significantly higher pre procedure VAS anxiety score (50.4 ± 26.5) compared to males (41.5 ± 26.8, p = 0.02). Other factors associated with higher levels of anxiety at different time points were age < 65 years, low level of education and an acute primary PCI. Conclusion: In the largest cohort to date, we examined anxiety among patients undergoing PCI or CAG was highest immediately around the procedure, particularly in patients aged < 65 years, of female gender, undergoing primary PCI, or with a lower level of education. Better pre-procedural information or pharmacological strategies may reduce anxiety in these patients.